Hubungan Status Gizi Dengan Gingivitis Pada Anak Umur 10 – 12 Tahun di SD Negeri Perumnas 3 Depok Yogyakarta - Hidayati, Siti; Sulistyani, Herastuti; Aziz, Shoimah Robie'Atu Yumni (Journal of Oral Health Care, 2019)
Nutritional status is a sign or a sideways that result from nutrient intake and nutrient expenditure seen through certain variables. Inadequate nutrition will cause tissue damage, infection and inflammation. Malnutrition significantly affects host immune resistance to bacterial growth. The presence of bacteria in plaque can cause gingival inflammation (gingivitis). This research aims to investigate the correlation between nutritional status with gingivitis in children aged 10-12 years in SD Negeri Perumnas 3 Depok, Yogyakarta. This research is analytic observational with a cross-sectional research design. This research was conducted in November 2017. The population in this study were the students of grade IV, V and VI SD Negeri Perumnas 3 Depok, with a sample of 45 people. Sampling uses purposive sampling. Data collection of nutritional status uses Body Mass Index (BMI) and gingivitis using Gingival Index according to Loe Stillness 1963. Data analysis use contingency coefficient. Most of the samples in children aged 10-12 years were the good nutritional status of 73% and gingival status in children mostly experienced gingivitis of 93%. Based on the statistical test the contingency coefficient showed no relation between nutritional status and gingivitis (p = 0, 860) There is no relationship between nutritional status with gingivitis in children aged 10-12 years